(untitled) (Asian Journal of Medical and Biological Research, 2021)
Gastroenteritis is a disorder of gastrointestinal tract with symptoms of mainly diarrhea, vomiting and abdominal cramps, which is major cause of child morbidity and mortality, caused by mostly viruses, and bacteria, protozoa, etc. E. coli O157, Salmonella spp. and Shigella spp. play a significant role along with different sociodemographic and epidemiologic risk factors to cause bacterial gastroenteritis (BGE) in children. This study aimed to assess the burden of gasteroenteritis caused by the mentioned three bacteria, and contribution of several risk factors causing the disease in children. Stool specimens from hospitalized children were obtained along with sociodemographic and epidemiologic data. Bacterial pathogens from stools were recovered by using selective media, biochemical and serological tests. We found 15% (17/116) of the clinically suspected gastroenteritis children were infected with Salmonella spp. (29%), Shigella spp. (59%) and E. coli O157 (12%). A chi-square test of all (116) data revealed that sex (p<0.05), dehydration (p=0.05), contact with the diarrheal patient (p<0.05), past episode of diarrheal illness (p<0.05) and vomiting (p<0.02), feeding practices like only breastfeeding (p<0.05), breastfeeding with subsequent feeding (p<0.05), subsequent feeding (p<0.05), weaning status (p<0.001), family diet (p<0.05), types of drinking water (p<0.002), Father’s education (p<0.05), occupation (p=0.05), and family income (p<0.001) were significantly associated with BGE. Determination of these potential risk factors will help to minimize the possibility of getting BGE and to reduce morbidity and mortality and also will aid to effective disease management and prevention of BGE outbreak in future. Asian J. Med. Biol. Res. 2021, 7 (2), 222-229